LIVER TRANSPLANTATION FOR EPITHELIOID HEMANGIOENDOTHELIOMA WITH DIFFUSE INTRAPERITONEAL METASTASES: A CASE REPORT - I. A. Porshennikov; A. Yu. Bykov; V. N. Pavlik; E. E. Shchekina; K. Yu. Beloborodov; K. A. Gryaznov; E. V. Lashchenkova; T. N. Pavlova (Вестник трансплантологии и искусственных органов, 2014)
We report the case of a young woman who underwent liver transplantation for epithelioid hemangioendothe- lioma with diffuse intraperitoneal metastases. We observe the 1-year survival without tumor progression on everolimus-based immunosuppression. The different therapies and the results of surgery for this disease are discussed in short literature review.